Neoliberal environments: False promises and unnatural consequences - March Corbella, Hug (Documents d'Anàlisi Geogràfica, 2008)
HEYNEN, Nick; MCCARTHY, James; PRUDHAM, Scott; ROBBINS, Paul Neoliberal environments: False promises and unnatural consequences Abingdon (Oxon, UK); Nova York: Routledge, 2007; 298 p. ISBN: 978-0-415-77148